[Rezension von: Collins, Paul, The Sumerians] - Podany, Amanda H. ca. 20./21. Jh.; Collins, Paul (2023)
The Sumerians. By Paul Collins. Lost Civilizations. London: Reaktion Books, 2021. Pp. 214, illus. $25. [Distributed by University of Chicago Press.]
Keywords: Rezension